Loneliness is related to facial emotion perception in people with HIV - Moka Yoo-Jeong; Rebecca E. Easter; Jennifer M. Coughlin; Raha M. Dastgheyb; Scott A. Langenecker; Gabriela Molestina; Juhi Patel; Skylar Rucci; Eran F. Shorer; Isabelle Thompson; Alejandra Woolsey; Tracey E. Wilson; et al. (Scientific Reports)
Abstract Loneliness, defined as unmet needs for intimate relationships (emotional loneliness) or larger social connections (social loneliness), is a risk factor for internalizing disorders common among people with HIV (PWH). While loneliness is associated with facial emotion perception (FEP)—the ability to recognize others’ emotional expressions—research has focused on healthier, younger populations, limiting its generalizability to PWH. Further, the extent to which emotional and social loneliness is associated with FEP has not been examined. As such, this study assessed the relationship between loneliness subtypes and FEP in 75 PWH (mean age = 59.4; 56% male; 77% Black). Participants completed the De Jong Gierveld Loneliness Scale and an FEP Task that measures recognition of happy, sad, angry, fearful, and neutral emotions. Emotional loneliness was associated with reduced neutral bias (r=− 0.28, P = 0.014) and lower overall accuracy (r=− 0.46, P < 0.001), including poorer recognition of fear, anger, happy, and neutral emotions. Social loneliness was related to greater inaccuracy in identifying negative emotions (r = 0.29, P = 0.011) and misperception of fear (r = 0.22, P = 0.049). Findings suggest that emotional and social loneliness are related to different aspects of FEP, underscoring the need for interventions targeting loneliness subtypes to improve FEP deficits and social-emotional functioning in PWH.